THU0314 Radiologic activity is the major determinant for physicians while deciding active disease in takayasu arteritis. (15th June 2017) - Kenar, G; Cetin, P; Yarkan, H; Zengin, B; Can, G; Birlik, M; Onen, F
Abstract : Background: There are no valid follow-up parameters in the assessment of disease activity in Takayasu arteritis (TA). Objectives: We investigated the impact of incorporation of vascular imaging into ITAS in the assessment of disease activity in TA. Methods: 52 patients who fulfilled the ACR criteria were included in the study. PGA, Kerr et al.'s criteria and ITAS2010/ITAS-A scores were evaluated in all patients in serial visits. All the patients were followed using 3–6 monthly B-mode/Doppler ultrasonography (USG) and 6–12 monthly magnetic resonance angiography (MRA). Radiological activity (Rad) was defined based on the presence of any of the 3 parameters including new vessel involvement by any technique (5 points), increase in vessel wall thickness on USG (3 points) and vessel wall edema on MRA (3 points).Then we incorporated these scores with ITAS-A to obtain a composite disease activity index (ITAS2010-A-Rad) (Table 1). Active disease was defined as ITAS-A-Rad >4 points. Results: Total 410 visits of 52 TA patients (mean age 50.7 yrs, F: 92.3%, mean follow-up duration:6.4±2.9 yrs) were evaluated. Radiological assessment was done in 359 visits (by USG in 271 and by MRA in 190). Patients were categorized as having active disease in 194 visits (47.4%) according to PGA and 72 visits (17.5%) according to Kerr et al. criteria.The agreement between them was fair (66%, κ: 0.29). Radiological activity was determined in 105 out of 359 visits (29.2%). The total agreement between radiological activity and Kerr at al. criteria was 83% (κ: 0.58). It was found to be 76% (κ: 0.52) between radiological activity and PGA. Mean ITAS-A-Rad scores were found to be significantly higher in visits with active disease compared to visits with inactive disease according to both PGA and Kerr et al. criteria (Table 2). The ITAS-A-Rad was significantly correlated with all the other activity parameters including ITAS2010, ITAS-A, and APRs. There were 43 visits with new vessel involvement by any radiologic technique; all visits included patients with active disease based on both PGA and Kerr et al. criteria. Whereas in 50% of these visits, patients had normal CRP, and %49 had normal ESR. The agreement between ITAS2010 and PGA was fair (69%, κ: 0.38).When APR was added (ITAS-A), it did not improve (68%, κ: 0.34). But the agreement between ITAS-A-Rad and PGA (72%, κ: 0.50) and also Kerr et al. criteria (82%, κ: 0.56)was found to be moderate. Interestingly, when only USG (ITAS-A-USG) or only MRA (ITAS-A-MRA) was used, the agreement with PGA was remained unchanged (73%, κ: 0.45 and 76%, κ: 0.52, respectively). When responsiveness to change of ITAS-A-Rad score was evaluated by serial visits of patients, it was found that the mean value of the score was discriminative for activity according to PGA in 9 of 11 visits (Figure 1 ). Conclusions: The results of this study suggest that ITAS-A-Rad may be used to be a valuable foIlow-up parameter in the assessment of disease activity. Disclosure of Interest: None declared